2010
DOI: 10.1130/g30576.1
|View full text |Cite
|
Sign up to set email alerts
|

Bedrock fracture control of glacial erosion processes and rates

Abstract: The importance of rock type and tectonic history on rates of glacial erosion, and the relative roles of glacial quarrying and abrasion, are poorly understood. We use concentrations of cosmogenic 10 Be in glacial polish and measurements of bedrock fracture spacing to explore the relationship between erosion rates and rock fracturing at 23 sites along Tuolumne River valley and fi ve sites in Tenaya Canyon in Yosemite National Park, California, USA. Most sites yield 10 Be concentrations that can be best explained… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
136
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 165 publications
(148 citation statements)
references
References 32 publications
(17 reference statements)
6
136
0
Order By: Relevance
“…where K is a constant that characterizes the erodibility of the subglacial material (Laitakari et al, 1985;MacGregor et al, 2009;Duhnforth et al, 2010) and l is another constant generally equal to 1 (Table 1). While a few recent studies have used more sophisticated rules for erosion (MacGregor et al, 2009;Iverson, 2012), this is the same rule as used in previous ICE-Cascade and other glacially influenced, landscape evolution models (e.g., Braun et al, 1999;Herman and Braun, 158 R. M. Headley and T. A. Ehlers: Ice flow models and glacial erosion over multiple glacial-interglacial cycles 2008; Kessler et al, 2008;Egholm et al, 2012b;Yanites and Ehlers, 2012).…”
Section: Glacial Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…where K is a constant that characterizes the erodibility of the subglacial material (Laitakari et al, 1985;MacGregor et al, 2009;Duhnforth et al, 2010) and l is another constant generally equal to 1 (Table 1). While a few recent studies have used more sophisticated rules for erosion (MacGregor et al, 2009;Iverson, 2012), this is the same rule as used in previous ICE-Cascade and other glacially influenced, landscape evolution models (e.g., Braun et al, 1999;Herman and Braun, 158 R. M. Headley and T. A. Ehlers: Ice flow models and glacial erosion over multiple glacial-interglacial cycles 2008; Kessler et al, 2008;Egholm et al, 2012b;Yanites and Ehlers, 2012).…”
Section: Glacial Modelsmentioning
confidence: 99%
“…In addition, sediment that is eroded then deposited is reincorporated into the model with the same erodibility as the original bedrock. A variety of research related to modeling and field data of different erosional systems has shown that the rock erodibility, whether this varies due to fracturing, rheology, or composition, can have a significant effect on the ultimate form of the landscape (Duhnforth et al, 2010;Ward et al, 2012).…”
Section: Model Caveats and Limitationsmentioning
confidence: 99%
“…Cuesta-type landscapes can be modified by glacial erosion, but the resultant 'hard-bed landform assemblage' has a very different geomorphology, commonly characterized by bedrock megagrooves (e.g. Zumberge, 1954;Krabbendam and Bradwell, 2011;Eyles, 2012 (Mathes, 1930;Dühnforth et al, 2010).…”
Section: )mentioning
confidence: 99%
“…Equally, numerous studies suggest a strong link between the presence of preexisting mechanical discontinuities (bedding and joints) and plucking (e.g., Gordon, 1981;Rastas and Seppälä, 1981;Rea, 1994;Glasser et al, 1998). Dühnforth et al, (2010) showed that within one rock type (granodiorite) that underwent valley glaciation in Yosemite, areas of close joint spacing experienced faster, deeper glacial erosion than areas of wide joint spacing; and they attributed this to enhanced plucking in areas of close joint spacing. Hardness and joint density are therefore expected to provide strong controls on the mode of erosion (i.e., abrasion vs. plucking).…”
Section: Introductionmentioning
confidence: 99%